An Analysis of Teacher pedagogical competence in Teaching English at SMK PGRI 3 Kota Serang - Clara Suci Shelly; Ida Nuraida; Fadilla Oktaviana (FKIP, Universitas Banten Jaya, 2020)
Teacher is one of actor who has the important position to determine the success key of process of learning. Although, the factors that can affects the process of learnnig is not only based on the teacher itself. But as an agent of educator in formal educational institution, the teacher can bring the biggest impact for all of the students. Because as we known, to create the best quality in process of learning, it always need the qualify and professional teacher. There are four competence that should be mastering by teachers, to make themselves be qualify . One of the competence is pedagogical competence. This one, is competence that make the teacher profession is different from the other profesion. This research aimed to describe the ability of teacher in mastering pedagogical competence, and also the process of implementation of pedagogical competence in teaching English at SMK PGRI 3 Kota Serang. This research is one the kind qualitative research with the descriptive approach. To collect data related to the subject that being studied in this research, the writer used some of techniques such as observation, questionnaire, interview and some of the research documentations. This research used three of English teacher as a sample research. For the result of this research it can see based on the result of observation sheet that show is around 65.625% for the implementation of pedagogical competence in the process of teaching English. And, for the result of questionnaire get the 70% for score in ability of teacher in mastering pedagogical competence. Based on this research, it can conclude that the ability of teacher in mastering pedagogical competence and implementation of it in teaching English are still include on the good category.